Analisis Kualitas Packaging Produk Terhadap Preferensi Dan Kesesuaian Produk Mie Instan - Novia Anggelina; Riska Susilawati; Syamsul Hidayat (Manajemen Kreatif Jurnal, 2025)
Instant noodles, categorized as part of ready-to-eat cuisine, represent a form of food that is conveniently packaged, easily served, practical, and prepared in a straightforward manner. Despite their convenience, instant noodles fall short of being considered a comprehensive food option due to their inability to fulfill the body’s well-rounded nutritional requirements. A typical serving of instant noodles primarily consists of elevated levels of carbohydrates and protein, yet lacks sufficient energy, fiber, vitamins, and minerals. The consumption of instant noodles is driven by the time constraints faced by a majority of consumers, preventing them from indulging in a complete meal and preparing it from scratch. Regularly consuming instant noodles may pose health risks and hazards, given their inclusion of preservatives and low nutritional content. This study employs quantitative research methods, adhering to scientific principles by being concrete, empirical, objective, measurable, rational, and systematic. Quantitative approaches prioritize the analysis of numerical data, subsequently processed through suitable statistical methods. In conclusion, the statistical analysis conducted reveals that both preference (X1) and suitability (X2) jointly exert a significant impact on packaging quality (Y) within the scope of this research. However, it is crucial to note that 51.1% of the variation in Y remains unexplained by these two independent variables, suggesting that other factors may also contribute to determining the quality of packaging.